EFFECT OF FERTILITY ASSOCIATED PROTEIN ON OXIDATIVE ,nR1-1 STRESS OF BOVINE SPERM CELLS - KARUNAKARAN, M; DEVANATHAN, T G; KULASEKAR, K; SRIDEVl, P; JAWAHAR, TILAK PON; LOGANATAHSAMY, K; DHALI, A; SELVARAJU, S (The Indian Journal of Animal Reproduction, 2023)
The present study addressed the effects of fertility associated protein on oxidative stress in frozen thawed bullspermatozoa. The frozen semen samples of 22 bulls were thawed at 37° C in a water bath and oxidative stresswas measured indirectly by estimating malondialdehyde (MDA) level at immediate post thaw, 60, 120 and 180min of incubation. To find whether addition of fertility associated protein would control the oxidative stress of thesperm cells, 25 μg of 28 - 30 kDa heparin binding protein of the sperm membrane was added to the thawed semensamples and MDA levels were estimated. MDA level was significantly lower (P < 0.01) in fertility associatedprotein treated semen sample than the untreated control semen at 60 min (1.95 ± 0.11 vs 2.85 ± 0.12), 120 min(2.40 ± 0.12 vs 3.20 ± 0.20) and 180 of incubation (2.99 ± 0.15 vs 4.31 ± 0.32). It was concluded that 28- 30 kDaheparin binding protein of the sperm membrane could help in controlling the oxidative stress of the sperm cellsduring incubation.
Keywords: Bull; Semen; Oxidative stress; Lipid peroxidation; Malondialdehyde; Fertility associated protein